Design of Sales Purchasing and Inventory Information System at Kopi Akhir Zaman - Chintya Mahdiyyah Akbar Santoso; Latiffah Rabbani; Sembiring, Salsalina; Hita (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The development of information technology is currently very influential in the business world to improve performance, both in trade and service businesses. Kopi Akhir Zaman is one of the cafes in the city of Medan. The menu available includes various types of drinks such as Americano coffee, long black, Japanese black, coffee latte, double espresso, non-coffee versions such as red velvet, black oreo, taro, lychee milk. This cafe also sells food such as fried rice, instant noodles, fried bread, French fries and many other types of food. The increase in the Kopi Akhir Zaman business has made it difficult for cafe owners to serve orders every day, as well as in managing inventory and estimating purchases of goods from suppliers. This study was conducted to analyze and design an information system that can help cafe owners manage sales, purchasing and inventory transactions. The method used in this research to design this system is the System Development Life Cycle (SDLC). With a design that is designed in the form of a simple and user-friendly display design that makes it easy for users to carry out the sales, purchasing and inventory processes. The results of this study can be useful as recommendations as a basis for developing a proposed system.